Persepsi dan Praktik Mahasiswa Jurusan Bahasa Inggris terhadap Pemanfaatan Media Sosial untuk Meningkatkan Speaking Skill - Endang Setiyo Astuti; Sri Fatmaning Hartatik (Universitas Insan Budi Utomo, 2023)
This survey-based research investigates the perceptions and practices of English Language Study Program students regarding the utilization of social media to enhance their speaking skills. The aim is to explore how the students perceive and engage with social media platforms as tools for improving their speaking abilities. The study employs a survey method, utilizing a questionnaire as the primary data collection instrument. The participants consist of English Language Study Program students who are in the 5th semester of an institution in Malang. The collected data is analysed through descriptive statistical analysis. The findings reveal that a significant proportion of the students hold positive perceptions towards the use of social media for enhancing their speaking skills. They perceive social media as a convenient and accessible platform for language learning, providing them with opportunities to practice speaking, access authentic language resources, and engage in meaningful interactions with other English speakers. Common practices among the participants include joining language learning communities, following language learning accounts, and participating in speaking challenges or discussions on social media platforms. However, the survey also highlights some challenges and limitations associated with the use of social media for speaking skill improvement. These include concerns regarding the authenticity of language input, potential distractions, and the need for self-regulation in selecting reliable language learning resources on social media. These findings contribute to the understanding of students' perspectives on the utilization of social media for speaking skill enhancement. The results suggest that social media platforms can serve as valuable supplementary tools for practicing speaking and creating a language-rich environment outside the classroom. To optimize the benefits of social media for speaking skill development, it is recommended that language educators integrate social media-based activities into their teaching approaches and provide guidance on effective and responsible use of social media for language learning purposes.